Meropenem-Vaborbactam vs. Best AvailableTherapy for Carbapenem-ResistantEnterobacteriaceae Infections in TANGO II: PrimaryOutcomes by Site of Infection - Wunderink, Richard; Giamarellos-Bourboulis, Evangelos; Rahav, Galia; Mathers, Amy; Bassetti, Matteo; Solomkin, Joseph; Alexander, Elizabeth; Loutit, Jeffrey S; Zhang, Shu; Dudley, Michael N; Kaye, Keith S (Open forum infectious diseases, 2017)
Abstract Background Meropenem-vaborbactam (M-V) is a β-lactamase inhibitor combination active against Klebsiella pneumoniaecarbapenemase (KPC)-producing CRE. Few clinical trials of new agents have been conducted in patients with CRE. Methods TANGO II is a randomized, Phase 3, open-label trial in patients with infections due to known or suspected CRE, including complicated urinary tract infection (cUTI), acute pyelonephritis (AP), HABP/VABP, bacteremia, or complicated intra-abdominal infection (cIAI). Eligible subjects were randomized 2:1 to monotherapy with M-V or Best Available Therapy (BAT) for 7–14 days. BAT could include (alone or in combination): a carbapenem, aminoglycoside, polymyxin B, colistin, tigecycline or ceftazidime-avibactam (monotherapy only). Enrollment was stratified by infection type and geographic region. Endpoints differed by infection: overall success (clinical cure + microbial eradication) in cUTI/AP, 28-day all-cause mortality in HABP/VABP + bacteremia, and clinical cure in cIAI. It was not powered for inferential statistical testing; results are presented descriptively. Results 72 patients were enrolled: 43 (59.7%) had baseline CRE and comprised the microbiologic CRE modified intent-to-treat population (mCRE-MITT, primary population). In mCRE-MITT, 20 had bacteremia, 15 had cUTI/AP, 5 had HABP/VABP, and 3 had cIAI. Conclusion In this first prospective comparative trial of a β-lactam/β-lactamase inhibitor combination as monotherapy of CRE infections, M-V showed consistent improvement over BAT in efficacy endpoints across infections, and improved safety/tolerability. M-V appears to be an improved treatment option for CRE infections. Disclosures R. Wunderink, The Medicines Company: Consultant and Investigator, Consulting fee and Research grant; G. Rahav, MSD: Consultant, Investigator and Speaker’s Bureau, Consulting fee, Research grant and Speaker honorarium; Pfizer: Consultant, Investigator and Speaker’s Bureau, Consulting fee, Research grant and Speaker honorarium; Astellas: Consultant, Investigator and Speaker’s Bureau, Consulting fee, Research grant and Speaker honorarium; A. Mathers, Accelerate Diagnostics: Consultant, Consulting fee; The Medicines Company: Consultant, Consulting fee; Zavante Therapeutics: Research Contractor, Research support; M. Bassetti, MSD: Consultant, Research Contractor and Speaker’s Bureau, Consulting fee, Research grant and Speaker honorarium; Pfizer: Consultant, Research Contractor and Speaker’s Bureau, Consulting fee, Research grant and Speaker honorarium; Astellas: Consultant and Speaker’s Bureau, Consulting fee and Speaker honorarium; AstraZeneca: Consultant and Speaker’s Bureau, Consulting fee and Speaker honorarium; The Medicines Company: Consultant, Consulting fee; Tetraphase: Consultant and Speaker’s Bureau, Consulting fee and Speaker honorarium; Angelini: Consultant and Speaker’s Bureau, Consulting fee and Speaker honorarium; Basilea: Consultant and Speaker’s Bureau, Consulting fee and Speaker honorarium; Achaogen: Consultant, Consulting fee; Paratek: Consultant, Consulting fee; J. Solomkin, Merck: Consultant, Consulting fee; Tetraphase: Consultant, Consulting fee; 3M: Consultant, Consulting fee; Arsanis: Consultant, Consulting fee; Department of Defense: Research Contractor, Research support; E. Alexander, The Medicines Company: Shareholder, Salary; J. S. Loutit, The Medicine’s Company: Employee and Shareholder, Salary; S. Zhang, The Medicines Company: Shareholder, Salary; M. N. Dudley, The Medicine’s Company: Employee and Shareholder, Salary; K. S. Kaye, Xellia: Consultant, Consulting fee; Merck: Consultant and Grant Investigator, Consulting fee and Research support; The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support Efficacy by Infection Type M-V (N = 28) n/N’ (%) BAT (N = 15) n/N’ (%) Bacteremia + HABP/VABP All-Cause Mortality, Day 28 4/16 (25.0%) 4/9 (44.4%) cUTI/AP Overall Success at End of Therapy (EOT) 8/11 (72.7%) 2/4 (50%) Overall Success at Test of Cure (TOC, EOT + 7 d) 3/7 (42.9%)* 2/4 (50%) cIAI Clinical Cure at TOC 1/1 (100%) 0/2 (0) *4 M-V subjects were indeterminate/not assessed at TOC. AEs occurred in 84.4% of M-V patients vs. 92% on BAT. M-V was associated with fewer drug-related AEs (24.4% vs. 44%), severe AEs (13.3% vs. 28%), and serious AEs (33.3% vs. 44%) vs. BAT.